2023
DOI: 10.1177/14680874231155571
|View full text |Cite
|
Sign up to set email alerts
|

Influence of thermal effect in piston skirt lubrication considering thermal deformation of piston and cylinder liner

Abstract: With the development of high-strength marine diesel engines, piston skirt lubrication plays an increasingly important role. In this study, to ensure that the mixed lubrication can be applied, the contact of the PS corner and CL is simplified to a spring–damper system. A coupled dynamical–tribological numerical model of a piston skirt is proposed by combining mixed lubrication and the secondary motion of the piston. The model is then used to study how the thermal effect of the piston skirt-cylinder liner fricti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…F contact,rad = F fric,rad + F gas,rad + F tension (7) The equilibrium equation for the bending moment of the ring section around the form center M is given as follows:…”
Section: The Piston Ring Group Dynamic Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…F contact,rad = F fric,rad + F gas,rad + F tension (7) The equilibrium equation for the bending moment of the ring section around the form center M is given as follows:…”
Section: The Piston Ring Group Dynamic Modelmentioning
confidence: 99%
“…Studies [4,5] have shown that an increase in the degree of irregular cylinder-bore deformation would lead to an increase in friction loss between the piston and cylinder bore. The friction between the piston assembly and cylinder bore accounts for half of the total friction loss of the engine [6,7]. Research has shown that for every 10% increase in engine friction loss, fuel consumption would increase by 3% to 5%, and the engine's effective output power would also decrease accordingly.…”
Section: Introductionmentioning
confidence: 99%